Food writings in a postmodern society: a discourse analysis of influencer and celebrity chef cookbooks in Belgium - Proesmans, Viktor L. J.; Vermeir, Iris; Teughels, Nelleke; Geuens, Maggie (Frontiers in Communication, 2023)
Introduction The landscape of food writings has undergone a significant transformation, shifting from traditional informational cookbooks to hybrid edutaining cookbooks authored by celebrity chefs and influencers. To gain a better understanding of this evolution, we conducted a discourse analysis to examine the proclamations made by cookbooks authored by celebrity chefs and influencers and their alignment with our society. Methods We conducted a critical discourse analysis on 18 best-selling cookbooks published in Flanders (Belgium) between 2008 and 2018. Applying Fairclough's three-dimensional framework, we conducted text, process, and social analyses to delve into the content and context of the cookbooks. Results Our analysis reveals that modern cookbooks not only provide information but also aim to inspire and entertain readers. They adopt a personal discourse that emphasizes shared values and authenticity. Celebrity chefs focus on traditional aspects, such as family, tradition, and the joy of cooking, while influencers offer lifestyle advice centered on postmodern values, including moral choice, achievement, fulfillment, and personal responsibility. Additionally, influencers take an anti-establishment stance by criticizing “conventional science” and processed food, reflecting the growing societal distrust toward food science and the food industry. Discussion The shift from traditional informational cookbooks to hybrid edutaining cookbooks authored by media icons such as celebrity chefs and influencers is apparent based on our analysis. These contemporary cookbooks not only provide recipes but also serve as outlets for inspiration and entertainment. Furthermore, the discourse found in modern cookbooks reflects the prevailing societal trends of our postmodern and individualistic era.